Neuroendocrine Abnormalities Following Traumatic Brain Injury: An Important Contributor to Neuropsychiatric Sequelae - Molaie, Amir M.; Maguire, Jamie (Frontiers in Endocrinology, 2018)
Neuropsychiatric symptoms following traumatic brain injury (TBI) are common and contribute negatively to TBI outcomes by reducing overall quality of life. The development of neurobehavioral sequelae such as concentration deficits, depression, anxiety, fatigue, and loss of emotional well-being has historically been attributed to an ambiguous “post-concussive syndrome,” considered secondary to frank structural injury and axonal damage. However, recent research suggests that neuroendocrine dysfunction, specifically hypopituitarism, plays an important role in the etiology of these symptoms. This post-head trauma hypopituitarism (PHTH) has been shown in the past two decades to be a clinically prevalent phenomenon, and given the parallels between neuropsychiatric symptoms associated with non-TBI induced hypopituitarism and those following TBI, it is now acknowledged that PHTH is likely a substantial contributor to these impairments. The current paper seeks to provide an overview of hypothesized pathophysiological mechanisms underlying neuroendocrine abnormalities after TBI, and to emphasize the significance of this phenomenon in the development of the neurobehavioral problems frequently seen after head trauma.